The Relationship Between Employee Empowerment and Subjective Wellbeing: Evidence from Services-Based SMEs in Pakistan - Nimra Ali Khokher; Abdul Raziq (The Lahore Journal of Business)
Employee empowerment plays a key role in the management of talented personnel: it enables an organization to use workers’ skills and abilities in a way that enhances the performance of both employer and employee. Based on a survey of 349 small and medium enterprises in Quetta, this study examines the impact of employee empowerment on employees’ subjective wellbeing, which is measured in terms of affective and cognitive components. Its results indicate that employee empowerment has a significant and positive impact on employees’ subjective wellbeing, implying that senior managers should prioritize this aspect of human resource management.